Degradation behavior of carbon fiber reinforced plastic (CFRP) under microwave dielectric heating - Nguyen, Phuong Ngoc Diem (Animo Repository, 2010)
Carbon fiber reinforced plastic (CFRP) composites are used increasingly in many industrial applications due to their unique combination of characteristics. Currently, the main obstacles for widespread industrial applications of CFRPs are the lack of a complete understanding of CFRPs, the difficult degradation processes due to their high strength and thermal resistance, and their price. In keeping with the development of novel technologies, a large amount of CFRPs is being consumed in industries consequently, the amount of CFRP waste is increasing day by day. Hence, it is necessary to find a better way to treat CFRP wastes faster and more effectively, and to estimate the reduction in bending strength and elastic modulus values of CFRP since these mechanical properties represent the extensive and intensive properties. The author has shown that CFRPs, with reinforced carbon fiber (a good microwave absorber), can be degraded easily under microwave irradiation. Microwave can reduce the values of CFRPs bending strength and elastic modulus at short radiation time. After the application of microwave heating, CFRP wastes could be treated more easily by using regular ways of treating plastic wastes, such as recycling or land-fill. For CFRP medical wastes, microwave can kill all of the hazardous microorganisms. This research aimed to study the effect of microwave irradiation on unidirectional CFRP (UD-CFRP) and Cloth-type CFRP composites by comparing the values of bending strength and elastic modulus of the CFRP samples before and after the microwave process and through morphological study. In addition, the temperature profiles of CFRP during the microwave process were studied to understand clearly the reaction of microwave on the composites. The results from UD-CFRP showed that the degradation of 60% fiber volume fraction (Vf ) UD-CFRP samples occurred earlier than that of 65% Vf UD-CFRP samples on both 0 and 90 degree fiber alignments. The microwave irradiation caused vii De La Salle University the reduction of CFRPs mechanical properties. The highest reduction was on 65% Vf samples with 0o CF alignment under 400W: 75% reduction of bending strength and 25% decrease of the elastic modulus. The temperature of 60% Vf UD-CFRP samples increased faster and reached a higher value (200oK at channel 3, 200 W, 400 sec) as compared to that of 65% Vf UD-CFRP (160oK at channel 3, 200 W, 400 sec). Cloth-type CFRP was tested under 400 W microwave irradiation under different durations of radiation time. The results showed that the % weight loss of 195oC Tg, 10 layers, and 3k filaments Cloth-type CFRP (Type C) samples reached 17% after 54 sec. However, it was 11% weight loss for 115oC, 3 layers, and 12k filaments Cloth-type CFRP (Type B) samples after 900 sec. The temperature of Type C Cloth-type CFRP increased faster and reached a higher value as compared to that of Type B. The maximum reduction in mechanical properties of Type B and Type C occurred after 700 sec and 54 sec, respectively. The results from the simulation study showed that FDTD method and Boltzmann equation can be combined to predict the temperature distribution of CFRP under microwave irradiation. The simulated and the measured temperature curves were in good agreement. In almost all cases, the coefficient of determination values, R2, were over 0.9 (90%). For UD-CFRP, small deviations between the simulated and the measured temperatures were observed as follows: 2oK at channel 1, 8oK at channels 2 and 3, and 16oK at channel 4 for both 210 W and 350 W. The simulation results for Cloth-type CFRP showed small deviations from 3% to 13%.